UMA ABORDAGEM COM PROFISSIONAIS DA EQUIPE DE ENFERMAGEM SOBRE ÚLCERA POR PRESSÃO - Pellenz, Neida L. K.; Nascimento, Kauana d.; Perdossini, Leila G. d. B.; Dalmolin, Indiara S.; Ianzer, Cleni R. C. H. (Salão do Conhecimento, 2013)
Resumo